Retroperitoneoscopic surgical resection of a crossed ectopic non-functioning multicystic kidney associated with a severe ureteral dilation. A new surgical approach and literature review - Peranzoni Francesca; Birraux Jacques; Sommer Christelle; Sanchez Oliver (Urology Case Reports)
After horseshoe kidney, crossed renal ectopia (CRE) is the most common fusion anomaly of the kidney, with an incidence of 1:7000 autopsies. Most frequently the left kidney is the crossed ectopic component. In this article we present the first case of retroperitoneoscopic resection of a CRE and left ectopic multicystic dysplastic kidney with severely dilated ureter.